Effects of Music on Children’s Well-Being and Functioning - Zupet, Klemen (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter explores the impact of music on children's well-being and functioning. Music, a ubiquitous part of everyday life, exerts a wide range of effects. Recently, its use has expanded into the field of medicine, particularly through music therapy. While not all music listening qualifies as therapy, we have highlighted key findings related to therapeutic applications of music. Additionally, we delve into specific techniques and provide notable examples of how music therapy can be applied effectively.